(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Leprosy is an infectious disease caused by Mycobacterium leprae. This study aimed to know the risk factors of leprosy events in Bombana Regency in 2020. This study was an observational analytic study with case control study design. The sample of this study was all population of Bombana Regency in 2020. The case sample was the population diagnosed in the Leprosy Reporting Information System information reported by the Bombana Regency Health Office during 2017 to 2019, while the control sample was undiagnosed leprosy with matching based on age and gender. The total sample was 122 people (61 cases and 61 controls). Control sampling with systematic random sampling. Data analysed using by the STATA computer program with odds ratio test and multiple logistic regression. The results showed that BCG immunization (OR = 5.74, 95% CI = 1.95-16.89) and income (OR = 3.35, 95% CI = 1.34-8.38) were risk factors for occurrence leprosy, while population migration variables, education level, and humidity are not significant risk factors for leprosy. The study concluded that BCG immunization and income are risk factors for leprosy. The variable most at risk for leprosy is BCG immunization.